"Being speculative is better than to not do it at all": an interview with Natalie Zemon Davis. Issue 1 (13th July 2015) - Roitman, Jessica; Fatah-Black, Karwan
Abstract : Jessica Roitman and Karwan Fatah-Black meet Natalie Zemon Davis outside the University Library in Leiden for lunch and an interview. Although Davis is eager to study a Sranan-German dictionary she retrieved from the library, the three of them sit down for an engaging conversation on the historian's craft, its societal relevance and the future of early modern studies.